2000
DOI: 10.1083/jcb.148.1.173
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition by c-Fos Estrogen Receptor Activation Involves Nuclear Translocation of β-Catenin and Upregulation of β-Catenin/Lymphoid Enhancer Binding Factor-1 Transcriptional Activity

Abstract: Mouse mammary epithelial cells expressing a fusion protein of c-Fos and the estrogen receptor (FosER) formed highly polarized epithelial cell sheets in the absence of estradiol. β-Catenin and p120ctn were exclusively located at the lateral plasma membrane in a tight complex with the adherens junction protein, E-cadherin. Upon activation of FosER by estradiol addition, cells lost epithelial polarity within two days, giving rise to a uniform distribution of junctional proteins along the entire plasma membrane. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
168
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(182 citation statements)
references
References 66 publications
12
168
0
2
Order By: Relevance
“…It is very likely that for each promoter, a specific chromatin environment may differentially influence the functional activity of the multiprotein regulatory complex formed on DNA. We checked that the enhanced transcriptional activity of b-catenin did not result from a destabilization from the plasma membrane (see Supplementary data, Figure 2), as described previously in a different experimental setting relying on a prolonged activation of AP-1 over several days (Fialka et al, 1996;Eger et al, 2000). It is likely that the enhanced transcriptional activity resulted from the recruitment of nuclear b-catenin on DNA and the formation of one or several multiprotein complexes at TBE sites with enhanced transactivating capacity.…”
Section: Discussionmentioning
confidence: 75%
“…It is very likely that for each promoter, a specific chromatin environment may differentially influence the functional activity of the multiprotein regulatory complex formed on DNA. We checked that the enhanced transcriptional activity of b-catenin did not result from a destabilization from the plasma membrane (see Supplementary data, Figure 2), as described previously in a different experimental setting relying on a prolonged activation of AP-1 over several days (Fialka et al, 1996;Eger et al, 2000). It is likely that the enhanced transcriptional activity resulted from the recruitment of nuclear b-catenin on DNA and the formation of one or several multiprotein complexes at TBE sites with enhanced transactivating capacity.…”
Section: Discussionmentioning
confidence: 75%
“…Competition on cadherin binding, on the other hand, may release b-catenin from a protected junctional pool making it available for transactivation, degradation, or both (Miller and Moon, 1997;Salomon et al, 1997;Simcha et al, 1998). Such conditions most probably prevail during embryonal development when cells extensively modulate their junctions, when Wnt signaling is activated (Klymkowsky et al, 1999), or during epithelial mesenchymal transition that is associated with dramatic changes in junctional assembly (Eger et al, 2000). Future studies will have to unravel the details of this very complex, multimolecular regulation of b-catenin level and its signaling role in mammalian cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Behrens et al (1989) and many others demonstrated that epithelial cells acquire invasive qualities as a result of loss of E-cadherin-mediated adhesion. In an in vitro model of mammary cells, Eger et al (2000) showed that Fos up-regulates ␤-catenin and LEF-1 activity, followed by down-regulation of E-cadherin to activate EMT. This finding implicates LEF-1, a transcription factor usually activated by ␤-catenin, in the down-regulation of E-cadherin (Fig.…”
Section: Mechanisms That Produce Migrating Mesenchymal Cellsmentioning
confidence: 99%